Expectant Management of a Triploid Partial Molar Pregnancy at 26 Weeks' Gestation: A Case Report - Karen Wong; Mohannad Ali; Marc Stalder; Brigitte Bonin; Darine El-Chaâr (Thieme Medical Publishers, Inc., 2024)
Introduction Triploid partial molar pregnancies are not viable, and confer maternal risks including preeclampsia, hemorrhage, gestational trophoblastic neoplasia, and trophoblastic embolization. We report a case managed expectantly until 26 weeks' gestation in a patient requesting continuation of pregnancy.